Penentuan Harga Pokok Produksi Cengkeh di Catur Desa (Desa Gobleg, Desa Munduk, Desa Gesing, dan Desa Umejero) - Wiratama, agus ari; Dewi, Ni Wayan Yulianita (Universitas Pendidikan Ganesha, 2021)
This study aims to understand and reveal the determination of the cost of production of cloves among farmers in Catur Desa (Gobleg Village, Munduk Village, Gesing Village, and Umejero Village). This study used qualitative research methods. Data collection was done by means of interviews, observation and documentation. The method used in this research is descriptive qualitative with an empirical study approach. The results of this research. The calculation of the cost of goods manufactured by farmers does not use the existing theoretical basis, but they only remember the huge costs they have spent and calculate as much as they can. Each distributor has a predetermined basic price, but in reality farmers still use the cost of goods that has been determined from each collector (distributor) in each village. The implication of this research is that in practice the results of this study have positive implications for the parties involved in this research. With the determination of the cost of production carried out by the author, it can help petanni to calculate the cost of production which should be able to determine the profitability obtained by farmers. This research is very helpful later for farmers to start recording costs so that they can calculate the cost of production and find out the resulting profitability. In theory, the cost of goods manufactured theory states that the cost of goods manufactured is the basis for determining the selling price. To determine the selling price, it is important for farmers to know the costs required to produce the cloves for sale..